PENERAPAN MODEL PEMBELAJARAN FISIKA SETTING KOOPERATIF TERPIMPIN (SKT) PADA SISWA KELAS XI IPA SMA NEGERI 1 MAJENE - Hamsyim Hammaali (Jurnal Sains dan Pendidikan Fisika, 2012)
Abstract. This research employs a pre-experimental design to examine the students’ learning achievement in the subject of material elasticity after being taught by using physics lesson of guided cooperative setting model. The population of this research was the entire second grade students of science class at SMA Negeri 1 Majene which was three classes consisted of 103 students. The sample of the research was taken randomly one out of three classes with 31 students as the number of samples.Data analysis used in this research was descriptive statistic analysis and inferential statistic analysis. Descriptive statistic was used to analyze the instructional instrument validity and to describe the students’ learning achievement, and the inferential analysis was used to test the hypothesis by using t-test. The result of the research reveal that: (1) response of second grade students of science class of SMA Negeri 1 Majene toward the instructional process and instructional model of physics of leaded cooperatif setting on the subject of material elasticity was meanly on the category of very satisfied; (2) learnig achievement of second grade students of science class at SMA Negeri 1 Majene on the subject of material elasticity after taught by using physics lesson model of leaded cooperative setting was significantly achieve the Minimal Completeness Criteria (MCC) on the degree of authenticity α=0.05. Abstrak.Penelitian ini menggunakan disain pra eksperimen, untuk melihat seberapa besar hasil belajar siswa dalam pokok bahasan elastisitas bahan setelah diajar dengan Model Pembelajaran Fisika Setting Kooperatif Terpimpin (SKT). Populasi  penelitian ini adalah seluruh siswa kelas XI IPA SMA Negeri 1 Majene yang berjumlah tiga kelas terdiri dari 103 siswa. Sedangkan sampel penelitiannya dipilih secara acak satu kelas dari tiga kelas tersebut dengan jumlah sampel 31 siswa. Analisis data yang digunakan dalam penelitian ini adalah analisis statistik deskriptif dan analisis statistik inferensial. Statistik deskriptif digunakan untuk menganalisis kevalidan perangkat pembelajaran dan mendeskripsikan hasil belajar siswa. Sedangkan analisis inferensial digunakan untuk menguji hipotesis dengan menggunakan uji “t”. Hasil dari penelitian ini menunjukkan bahwa: (1) respon siswa kelas XI IPA  SMA Negeri 1 Majene terhadap proses pembelajaran dengan model pembelajaran Fisika Setting Kooperatif Terpimpin (SKT) pada pokok bahasan elastisitas bahan rata-rata ada pada kategori sangat senang, (2) hasil belajar siswa kelas XI IPA SMA Negeri 1 Majene pokok bahasan elastisitas bahan sesudah diajar dengan model pembelajaran Fisika Setting Kooperatif Terpimpin (SKT) secara signifikan rata-ratanya mencapai  KKM  pada taraf nyata α = 0,05. Kata kunci: model pembelajaran fisika SKT, respon Siswa, hasil belajar, KKM